A review on the application, phytochemistry and pharmacology of Polygonatum odoratum, an edible medicinal plant - Jingyi Bi; Huiyong Fang; Jianyun Zhang; Litao Lu; Xian Gu; Yuguang Zheng (Journal of Future Foods, 2023)
Polygonatum odoratum is distributed in several countries around the world as a medicinal and dual-use plant, and its rhizomes are used in China as a traditional Chinese medicine, also as vegetables, foods, functional foods or tea, with a history of application for more than 2 000 years, with precise efficacy and no toxic side effects. However, few reviews are published on its chemical composition and its pharmacological effects. There are many components of P. odoratum, including steroidal saponins, homoisoflavanones, isoflavones, flavonoids, alkaloids, lignin, volatile oil, polysaccharides and lectins. In this review, recent advances of the history and consumption of P. odoratum, the types of chemical components, and the pharmacological effects manifested in antitumour and anticancer, antioxidant, slowing senescence, relieving fatigue and immune regulation are summarized and discussed. Presumably, the main active ingredients of the plant are homoisoflavanones, polysaccharides, saponins, and lectins. The review provides a reference for its development and utilization in the field of functional food and medicine in the future.